Non-aqueous electrolyte and lithium ion battery

By using a tetraoxa spirocyclic compound A with a larger molecular radius as an electrolyte additive in a lithium-ion battery, the problem of the electrolyte solidification and charge and discharge performance of the lithium-ion battery in an extremely low temperature environment is solved, and significantly improved low-temperature discharge performance and cycling performance are achieved.

CN119650857APending Publication Date: 2025-03-18ZHUHAI SMOOTHWAY ELECTRONICS MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868864.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing lithium-ion batteries solidify under extremely low temperature environments (especially when the temperature drops to -30℃), and the charge and discharge performance is greatly reduced, and there is a risk of internal short circuits and explosions, limiting the application of lithium-ion batteries in cold areas.

Method used

A non-aqueous electrolyte is used, which includes lithium salt, non-aqueous organic solvent and additives. The additive is a tetraoxa spirocyclic compound A. The molecular radius of this compound A is large, which can improve the dissociation degree of lithium ions in the electrolyte, improve conductivity, and form a thinner, uniform and dense SEI film on the surface of the electrode to inhibit the occurrence of side reactions of the electrolyte.

Benefits of technology

It significantly improves the discharge performance and cycling performance of lithium-ion batteries under low temperature conditions, reduces the ohmic resistance inside the battery, improves the transmission rate of lithium ions, reduces the heat generated during the charging and discharging process, and enhances the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650857A_ABST
    Figure CN119650857A_ABST
Patent Text Reader

Abstract

The invention discloses a non-aqueous electrolyte and a lithium ion battery, the non-aqueous electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive, the additive comprises a compound A shown in a formula 1, # imgabs0 #, M is selected from O = S = O or C = O, and R is selected from CH2, CHF or CF2. The molecular radius of the compound A is large, the dissociation degree of lithium ions in the electrolyte can be improved, so that the conductivity of the electrolyte is improved, ohmic resistance in the battery is reduced due to improvement of the conductivity, heat generated in the charging and discharging process is reduced due to low ohmic resistance, and the service life of the battery is prolonged. Meanwhile, the high-conductivity electrolyte is also beneficial to improving the migration speed of lithium ions at a low temperature; importantly, the compound A can also participate in formation of a thinner, uniform and compact SEI film on the surface of the electrode, so that side reaction of electrolyte is inhibited, interfacial film impedance and potential difference polarization in the charge-discharge process are reduced, the transmission rate of lithium ions is improved, and the discharge performance of the battery under the low-temperature condition can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a non-aqueous electrolyte and a lithium ion battery. Background Art

[0002] With the rapid development of production and life in human society, non-renewable energy such as oil and natural gas has been gradually depleted. At the same time, the use of these energy sources has led to serious problems such as air pollution and greenhouse effect. There is an urgent need to find new green energy to replace them. In this context, lithium batteries have emerged as a clean and efficient energy storage method. Lithium batteries are mainly divided into lithium-ion batteries, lithium metal batteries, lithium-air batteries and lithium-sulfur batteries. Among them, lithium-ion batteries were first commercialized by Sony in 1991 due to their high open circuit voltage, large specific capacity, long cycle life, high safety, low self-discharge rate, wide range of applications, no memory effect and environmental friendliness.

[0003] As an important component of the battery, the electrolyte is not only a "bridge" between the positive and negative electrode materials, but also a medium for transferring charges between the positive and negative electrodes. The characteristics of the electrolyte and its interaction with the positive and negative electrode materials have a significant impact on the overall performance of the battery. In order to develop lithium-ion batteries with high rate, high power, long cycle life and high safety, it is crucial to choose a suitable electrolyte. In view of the advantages of organosilicon electrolyte such as excellent ionic conductivity, non-toxicity, non-flammability, and high degradation potential, it shows great potential in extending battery cycle life, increasing energy density and enhancing safety. Therefore, the use of organosilicon compounds as electrolyte additives is an important method to improve battery performance; currently commercialized organosilicon additives include tris(trimethylsilyl) phosphate (TMSP) and polydimethylsiloxane (PDMS). However, in extremely low temperature environments, especially when the temperature drops to -30°C, existing commercial silicone additives cannot significantly improve the low-temperature performance of the battery. In this case, the electrolyte of the lithium-ion battery will solidify, the charge and discharge performance will be greatly reduced, the internal polarization of the battery will be serious, and there is a risk of internal short circuit and explosion. This seriously limits the application of lithium-ion batteries in cold areas and some places in winter, especially in the development and application of electric vehicles and aerospace fields.

[0004] Therefore, there is an urgent need for a non-aqueous electrolyte and a lithium-ion battery to solve the deficiencies of the existing technical problems. Summary of the invention

[0005] In view of the above problems, an object of the present invention is to provide a non-aqueous electrolyte and a lithium ion battery, wherein the non-aqueous electrolyte can enable the lithium ion battery to have better room temperature cycle performance and low temperature discharge performance.

[0006] To achieve the above objectives, the present invention provides a non-aqueous electrolyte in a first aspect, comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises a compound A shown in Formula 1,

[0007]

[0008] Wherein M is selected from O=S=O or C=O, and R is selected from CH 2 , CHF or CF 2 .

[0009] Compared with the prior art, the molecular radius of the compound A of the present invention is larger, which can increase the dissociation degree of lithium ions in the electrolyte, thereby improving the conductivity of the electrolyte. The improvement of conductivity reduces the ohmic resistance inside the battery. The lower ohmic resistance means that the heat generated during the charge and discharge process is reduced. At the same time, the high-conductivity electrolyte also helps to increase the migration speed of lithium ions at low temperatures; more importantly, compound A can also participate in the formation of a thinner, uniform and dense SEI film on the electrode surface, inhibit the occurrence of electrolyte side reactions, reduce the interface film impedance and the potential difference polarization during the charge and discharge process, and increase the transmission rate of lithium ions, thereby significantly improving the discharge performance of the battery under low temperature conditions. In addition, compound A can form a firm SEI film on the surface of the positive and negative electrode materials at the same time during the battery formation stage, inhibit a series of adverse reactions occurring at the electrolyte electrode interface during the charge and discharge process, maintain the structural stability of the active material, and thus improve the cycle performance of the battery.

[0010] Furthermore, the compound A of the present invention is at least one selected from compounds 1 to 3:

[0011]

[0012] Furthermore, the mass percentage of the compound A of the present invention in the non-aqueous electrolyte is 0.05-1.5%. Specifically, the mass percentage of the compound A in the non-aqueous electrolyte can be, but is not limited to, 0.05%, 0.06%, 0.07%, 0.08%, 1%, 1.2%, and 1.5%.

[0013] Furthermore, the additive of the present invention also includes a film-forming aid, and the film-forming aid is at least one of cyclopentenetrione, 1,3-propane sultone, 1,3-propylene sultone, and 1,4-butane sultone. The introduction of the film-forming aid can further improve the performance of the SEI film, making it more uniform and dense, and further improve the cycle life and safety of the battery.

[0014] Furthermore, the mass percentage of the film-forming aid of the present invention in the non-aqueous electrolyte is 0.5-1.2%. Specifically, the mass percentage of compound A in the non-aqueous electrolyte can be, but is not limited to, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 1.0%, or 1.2%.

[0015] Furthermore, the additive of the present invention also includes a positive electrode protection additive, which includes at least one of hexaethyldisilazane and hexapropyldisilazane. The positive electrode protection additive can form a stable protective film on the surface of the positive electrode material, which can effectively prevent the electrolyte from directly contacting the positive electrode material, thereby inhibiting metal dissolution and redox reaction, thereby further improving the cycle performance of the battery.

[0016] Furthermore, the mass percentage of the positive electrode protection additive of the present invention in the non-aqueous electrolyte is 0.2-1.4%. Specifically, the mass percentage of the positive electrode protection additive in the non-aqueous electrolyte can be, but is not limited to, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%.

[0017] Further, the lithium salt of the present invention includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium methanesulfonate, lithium trifluoromethylsulfonate, lithium fluorosulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), lithium bis(fluorosulfonyl imide), lithium diphosphate non-aqueous organic solvent, and lithium lower aliphatic carboxylate.

[0018] Furthermore, the mass percentage of the lithium salt of the present invention in the non-aqueous electrolyte is 6-25%; for example, the content of the lithium salt may be but is not limited to 6%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%.

[0019] Further, the non-aqueous organic solvent of the present invention includes at least one of ethyl propionate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, butyl propionate, ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Specifically, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 58-88%; for example, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte may be, but is not limited to, 58%, 65%, 69%, 72%, 78%, 80%, 85%, and 88%.

[0020] Correspondingly, the second aspect of the present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, and the above-mentioned non-aqueous electrolyte. The lithium ion battery has good cycle performance and low-temperature discharge performance.

[0021] Furthermore, the active material of the positive electrode of the present invention is a nickel-cobalt-manganese oxide material, and the nickel-cobalt-manganese oxide is LiNi x Co y Mn 1-x-y M z O 2 , wherein 0.6≤x<0.9, x+y<1, 0≤z<0.08, and M is at least one of Al, Mg, Zr and Ti. Preferably, the active material of the positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O 2 .

[0022] Furthermore, the active material of the negative electrode of the present invention includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, tin metal compounds; the lithium negative electrode may include metallic lithium or lithium alloys, wherein the lithium alloy may specifically be at least one of lithium silicon alloys, lithium sodium alloys, lithium potassium alloys, lithium aluminum alloys, lithium tin alloys and lithium indium alloys. DETAILED DESCRIPTION

[0023] In order to more clearly explain the purpose of the present invention, technical solutions and beneficial effects thereof, further description will be given below by specific examples. It should be noted that in the examples and reference examples, if no experimental conditions are particularly indicated, the conditions recommended by the standard operating procedures or manufacturers should be followed. In addition, if the specific supplier of the reagents or equipment used is not specified, then these materials and instruments are all products that can be routinely purchased on the market.

[0024] Specifically, compound 1, compound 2, and compound 3 can be prepared by the following method:

[0025] (1) mixing a reaction substrate and dichloromethane to form a first mixed solution;

[0026] (2) cooling the first mixed solution to -20 to 10° C.;

[0027] (3) adding silicon tetrachloride (the molar ratio of the reaction substrate to silicon tetrachloride is 1:0.45-0.5) dropwise to the cooled first mixed solution within 0.5-2.5 hours. After the addition is complete, the temperature of the first mixed solution is raised to room temperature, nitrogen is continuously introduced, and the reaction is stirred for 2-3 hours. When the acid value is 800-1300 ppm after sampling and determination, the reaction is stopped and filtered to obtain a crude product in the form of a white solid;

[0028] (4) mixing the crude product with dichloromethane to obtain a second mixed solution, and then slurrying and purifying the second mixed solution;

[0029] More specifically, the synthetic routes of compound 1, compound 2, and compound 3 are as follows:

[0030]

[0031] The reaction substrate can be prepared by the following method:

[0032] The dibasic acid is added to a tetrahydrofuran solution, and then 2.2 moles of trimethylsilyl chloride are added at 0°C. After heating to room temperature, the mixture is stirred for 30 minutes. Then, 2.2 moles of an acid-binding agent, triethylamine, is slowly added. After stirring for 1 hour, the mixture is filtered, and the solvent is evaporated and then distilled under reduced pressure to obtain a reaction substrate. Correspondingly, when the dibasic acid is methyl disulfonic acid (CAS No.: 503-40-2), reaction substrate 1 can be obtained; when the dibasic acid is fluoromalonic acid (CAS No.: 473-87-0), reaction substrate 2 can be obtained; and when the dibasic acid is malonic acid (CAS No.: 141-82-2), reaction substrate 3 can be obtained.

[0033] Example 1

[0034] This embodiment provides a non-aqueous electrolyte, and the preparation of the non-aqueous electrolyte includes: in a glove box (O 2 <1ppm,H 2 O<1ppm), ethyl propionate, ethyl acetate, diethyl carbonate, and γ-butyrolactone are mixed in a mass ratio of 4:3:1:3 to prepare 88.9g of a non-aqueous organic solvent, followed by adding 0.06g of compound 1, dissolving and stirring thoroughly, then adding 0.6g of 1,4-butane sultone and 0.24g of hexapropyldisilazane, stirring evenly, adding 10.2g of lithium hexafluorophosphate, and mixing evenly to obtain 100g of a non-aqueous electrolyte.

[0035] The formulations of the non-aqueous electrolytes of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1, wherein the preparation processes of the non-aqueous electrolytes of Examples 2-6 and Comparative Examples 1-2 are exactly the same as that of Example 1.

[0036] Table 1 Compositions of the non-aqueous electrolytes of the embodiments and comparative examples

[0037]

[0038] The non-aqueous electrolytes of Examples 1 to 6 and Comparative Examples 1 to 2 are applied to lithium-ion batteries. Specifically, the non-aqueous electrolytes are injected into the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2In a button lithium metal battery with lithium metal as the positive electrode and lithium metal as the negative electrode, it was charged 3 times at a constant current of 0.1C, then charged to 4.3V at a constant current of 0.5C, and discharged to 2.8V at a constant current of 0.5C. Then, the room temperature cycle performance and low temperature discharge performance of the lithium ion battery were tested according to the following test method, and the test results are shown in Table 2.

[0039] Normal temperature cycle performance:

[0040] At room temperature (25°C), the formed lithium-ion battery is charged to 4.3V at 0.5C constant current and constant voltage, with a cut-off current of 0.02C, and then discharged to 2.8V at 0.5C constant current. The 0.5C charge / 0.5C discharge cycle is repeated 200 times to evaluate the cycle performance. The cycle performance is calculated by the capacity retention rate of the following formula:

[0041] Capacity retention rate (%) = (discharge capacity of the 200th cycle / discharge capacity of the first cycle) × 100%. Low temperature discharge test:

[0042] At room temperature (25°C), the lithium-ion battery was charged and discharged at 0.5C / 0.5C (the discharge capacity is recorded as C 0 ), the upper limit voltage is 4.3V,

[0043] The formed lithium-ion battery was charged to 4.3V under 0.5C constant current and constant voltage conditions, and the lithium-ion battery was placed in a low-temperature box at 0℃, -20℃ and -30℃ for 4h, and discharged to 2.8V at 0.5C at the corresponding temperature: low-temperature discharge rate = recovery capacity / initial capacity × 100%.

[0044] Table 2 Lithium-ion battery performance test results

[0045]

[0046] As shown in Tables 1 to 2, compared with Comparative Examples 1 to 2, the lithium ion batteries of Examples 1 to 6 have better room temperature cycle performance and low temperature performance. This is because the non-aqueous electrolyte of the present invention contains compound A, which is a tetraoxasilicon spirocyclic compound. On the one hand, the molecular radius of this compound is large, which can increase the dissociation degree of lithium ions in the electrolyte, thereby improving the conductivity of the electrolyte. The improvement of conductivity reduces the ohmic resistance inside the battery. The lower ohmic resistance means that the heat generated during the charging and discharging process is reduced. At the same time, the high conductivity electrolyte also helps to increase the migration speed of lithium ions at low temperatures, thereby improving the low temperature performance of lithium ion batteries. On the other hand, compound A can participate in the formation of a thinner, uniform and dense SEI film on the electrode surface, inhibit the occurrence of electrolyte side reactions, reduce the interface film impedance and the potential difference polarization during the charging and discharging process, thereby increasing the transmission rate of lithium ions. Therefore, using compound A as an electrolyte additive can significantly improve the discharge performance of the battery under low temperature conditions. In addition, the tetraoxasilicon spiro compound can form a strong SEI film on the surface of the positive and negative electrode materials at the same time during the battery formation stage, inhibiting a series of adverse reactions occurring at the electrolyte electrode interface during the charge and discharge process, maintaining the structural stability of the active material, and thus improving the battery's cycle performance.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: The method comprises a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises a compound A shown in Formula 1, Wherein M is selected from O=S=O or C=O, and R is selected from CH2, CHF or CF2.

2. The non-aqueous electrolyte according to claim 1, characterized in that The compound A is selected from at least one of compounds 1 to 3:

3. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the compound A in the non-aqueous electrolyte is 0.05-1.5%.

4. The non-aqueous electrolyte according to claim 1, characterized in that The additives further include a film-forming aid, and the film-forming aid is at least one of cyclopentenetrione, 1,3-propane sultone, 1,3-propene sultone, and 1,4-butane sultone.

5. The non-aqueous electrolyte according to claim 4, characterized in that The mass percentage of the film-forming aid in the non-aqueous electrolyte is 0.5-1.2%.

6. The non-aqueous electrolyte according to claim 1, characterized in that The additives further include a positive electrode protection additive, and the positive electrode protection additive includes at least one of hexaethyldisilazane and hexapropyldisilazane.

7. The non-aqueous electrolyte according to claim 6, characterized in that The mass percentage of the positive electrode protection additive in the non-aqueous electrolyte is 0.2-1.4%.

8. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium methane sulfonate, lithium trifluoromethyl sulfonate, lithium fluorosulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), lithium bis(fluorosulfonyl imide), lithium diphosphate nonaqueous organic solvent, and lithium lower aliphatic carboxylate.

9. A lithium ion battery comprising a positive electrode and a negative electrode, characterized in that: It also includes the non-aqueous electrolyte according to any one of claims 1 to 8.

10. The lithium ion battery according to claim 9, characterized in that The active material of the positive electrode is a nickel-cobalt-manganese oxide material, wherein the nickel-cobalt-manganese oxide is LiNi x Co y Mn 1-x-y M z O2, wherein 0.6≤x<0.9, x+y<1, 0≤z<0.08, and M is at least one of Al, Mg, Zr and Ti.